2017
DOI: 10.1667/rr14647.1
|View full text |Cite
|
Sign up to set email alerts
|

Combined Therapy of Pegylated G-CSF and Alxn4100TPO Improves Survival and Mitigates Acute Radiation Syndrome after Whole-Body Ionizing Irradiation Alone and Followed by Wound Trauma

Abstract: Exposure to ionizing radiation alone or combined with traumatic tissue injury is a crucial life-threatening factor in nuclear and radiological incidents. Radiation injuries occur at the molecular, cellular, tissue and systemic levels; their mechanisms, however, remain largely unclear. Exposure to radiation combined with skin wounding, bacterial infection or burns results in greater mortality than radiation exposure alone in dogs, pigs, rats, guinea pigs and mice. In the current study we observed that B6D2F1/J … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 52 publications
2
37
0
Order By: Relevance
“…This radiation dose is a lethal dose causing 50% population death within 30 days postirradiation (LD 50/30 ) and has been used for previous publications on testing drug efficacy. 23,24,[31][32][33]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This radiation dose is a lethal dose causing 50% population death within 30 days postirradiation (LD 50/30 ) and has been used for previous publications on testing drug efficacy. 23,24,[31][32][33]…”
Section: Resultsmentioning
confidence: 99%
“…Male mice were not used in this study because of potential problems associated with male mouse aggression, such as fight wounds which were not desirable during the experimental period. Previous combined injury studies 23,24,[31][32][33] also used female mice for this reason. As such, we continued to conduct this study with female mice so that data collected could be compared with previous ones.…”
Section: Animal and Experimental Designmentioning
confidence: 99%
“…Many government agencies involved in national security and public health, including the U.S. FDA, have been searching for suitable radiation countermeasures for the treatment of H-ARS and GI-ARS for several decades (5-7). However, to date, only a limited number of medical options are available, including G-CSF and PEGylated G-CSF, as mitigators of H-ARS (8)(9)(10)(11). Therefore, the development of safe and effective radiation countermeasures is a priority project for the government.…”
Section: Discussionmentioning
confidence: 99%
“…Over several decades, the U.S. Department of Health and Human Services (specifically, National Institutes of Health and the Biomedical Advanced Research and Development Authority) has sought to investigate potential radiation countermeasures that are safe, easily administered and effective at reducing adverse health effects that occur after radiation exposure (5)(6)(7). Despite these ongoing efforts, as of 2015, only Neupogent (granulocyte colony-stimulating factor; G-CSF) and Neulastat (pegylated G-CSF) have been approved by the U.S. Food and Drug Administration (FDA) as radiation countermeasures for the treatment of H-ARS (8)(9)(10)(11). Recently, Leukinet (granulocyte-macrophage colony-stimulating factor; GM-CSF) was approved by the FDA as a radiomitigator to increase survival and to facilitate the recovery of white blood cells in adults and pediatric patients acutely exposed to a sub-lethal dose of radiation (12).…”
Section: Introductionmentioning
confidence: 99%
“…Stagnation in supportive therapy on ARS is the major current situation [ 16 ]. Through in vivo studies, it has been found that cytokines like granulocyte colony-stimulating factor (G-CSF), granulocyte-monocyte colony-stimulating factor (GM-CSF), pegylated G-CSF (pegfilgrastim), interleukin-11, interleukin-3, and erythropoietin can either reduce the duration of pancytopenia or improve outcomes [ 16 21 ]. Other supportive treatments include blood product transfusion, anti-infective therapy, and antiemetic drugs.…”
Section: Introductionmentioning
confidence: 99%